Maternal visual perception of children’s nutritional status and feeding style - Ikromi Dalimunthe; Tiangsa Sembiring; Rita Evalina (Indonesian Pediatric Society, 2021)
Background Mothers’ visual perception is an important determinant for their children’s nutritional status. Visual perception of their children’s nutritional status is believed to drive mothers to modify or apply certain feeding styles, which influence the probability of either optimal growth or malnutrition. Objective To determine if maternal visual perception of children’s nutritional status influences maternal feeding style. Methods The study was conducted in 3 kindergartens in Medan, North Sumatera, involving children aged 4-5 years and their mothers. Mothers filled three-part questionnaires, consisting of basic information, a series of body image sketches by a graphic artist to assess maternal visual perception, and the Parental Feeding Style Questionnaire (PFSQ) to assess maternal feeding style. Children’s body heights and weights were measured to assess their nutritional status. Results A total of 102 subjects were eligible for this study. Surprisingly, more than half of the mothers involved in our study misinterpreted their children nutritional status. Thus, there was no significant relationship between maternal visual perception, nor maternal misperception, and maternal feeding style. In fact, mothers tended to encourage their children to eat when they considered their children to have normal nutritional status. Conclusion Mothers’ visual perception does not influence feeding practice.